(Re)presenting Brunei Darussalam A Sociology of the Everyday - Kwen Fee, Lian; Carnegie, Paul J.; Hassan, Noor Hasharina (Asia in Transition, ISSN 2364-8260, 2023)
This thoughtful and wide-ranging open access volume explores the forces and issues shaping and defining contemporary identities and everyday life in Brunei Darussalam. It is a subject that until now has received comparatively limited attention from mainstream social scientists working on Southeast Asian societies. The volume helps remedy that deficit by detailing the ways in which religion, gender, place, ethnicity, nation-state formation, migration and economic activity work their way into and reflect in the lives of ordinary Bruneians. In a first of its kind, all the lead authors of the chapter contributions are local Bruneian scholars, and the editors skilfully bring the study of Brunei into the fold of the sociology of everyday life from multiple disciplinary directions. By engaging local scholars to document everyday concerns that matter to them, the volume presents a collage of distinct but interrelated case studies that have been previously undocumented or relatively underappreciated. These interior portrayals render new angles of vision, scale and nuance to our understandings of Brunei often overlooked by mainstream inquiry. Each in its own way speaks to how structures and institutions express themselves through complex processes to influence the lives of inhabitants. Academic scholars, university students and others interested in the study of contemporary Brunei Darussalam will find this volume an invaluable resource for unravelling its diversity and textures. At the same time, it hopefully stimulates critical reflection on positionality, hierarchies of knowledge production, cultural diversity and the ways in which we approach the social science study of Brunei. ‘I wish to commend the editors for bringing this volume to fruition. It is an important book in the context of Southeast Asian sociology and even more important for the development of our social, geographical, cultural and historical knowledge of Brunei.’ —Victor T. King, University of Leeds.
Keywords: Culture; Social sciences; Race; Anthropology of religion; Ethnology : Asia; Islam; Sociology of Culture; Society; Race and Ethnicity Studies; Anthropology of Religion; Asian Culture; Brunei : Social conditions; Brunei : Religion